Elevated Systemic and Intestinal Inflammatory Response Are Associated With Gut Microbiome Disorder After Cardiovascular Surgery - Xia, Xiong; Ni, Jiangjin; Yin, Shengnan; Yang, Zhipeng; Jiang, Haini; Wang, Chao; Peng, Jian; Wei, Hongkui; Wang, Xingyu (Frontiers in Microbiology, 2021)
Systemic inflammatory response after cardiovascular surgery is associated with poor prognosis, to which gut barrier impairment is related. To investigate whether perioperative changes of the gut microbiome are associated with systemic and intestinal inflammatory response, we examined changes of the gut microbiome, intestinal homeostasis, and systemic inflammatory response in cardiovascular patients before (Pre) surgery and on the first defecation day [postoperative time 1 (Po1)] or a week [postoperative time 2 (Po2)] postsurgery. Markedly, the enhanced systemic inflammatory response was observed in Po1 and Po2 compared with that in Pre. In line with inflammatory response, impaired gut barrier and elevated gut local inflammation were observed in Po1 and Po2. Microbiome analysis showed a remarkable and steady decline of alpha diversity perioperatively. In addition, microbial composition in the postoperation period was characterized by significant expansion of Enterococcus along with a decrease in anaerobes (Blautia, Faecalibacterium, Bifidobacterium, Roseburia, Gemmiger, [Ruminococcus], and Coprococcus), which were typically health-associated bacteria. Spearman correlation analysis showed microbiome disorder was associated with enhanced systemic inflammatory response and intestinal dysbiosis. These results suggest that microbiome disorder was related to disturbed gut homeostatic and subsequently elevates plasma endotoxin and systemic inflammatory response after cardiovascular surgery. This study not only highlights gut microbiome would be considered in future clinical practice but also proposes a promising perspective of potential diagnostic and therapeutic options for perioperative management of cardiovascular surgery patients.